Diagnostic and prognostic relevance of magnetic resonance imaging and electrophysiological findings in acute spinal ischemia - Artemis, Dimitrios; Wolf, Marc; Blahak, Christian; Szabo, Kristina; Hennerici, Michael G.; Fatar, Marc (Journal of stroke and cerebrovascular diseases, 2017)
OBJECTIVE: Our purpose was to classify the rare entity of spontaneous spinal ischemia with clinical, magnetic resonance-tomographic, and electrophysiological parameters to determine criteria for outcome prediction. METHODS: We analyzed the stroke registry database of the University Hospital Mannheim, Germany, from 2004 to 2010 for patients with a diagnosis of vascular spinal cord ischemia. RESULTS: Ten patients were identified (mean age 65 years [range 50-83], 5 women). In 5 patients an etiology was found. Spinal diffusion-weighted magnetic resonance imaging revealed acute ischemia in 7 patients at initial imaging and this diagnosis was confirmed during the first week in the remaining 3 patients. Electrophysiological studies showed abnormal motor evoked potentials (MEPs) in 8 patients and abnormal somatosensory evoked potentials (SSEPs) in 7 patients. After rehabilitation, 5 patients had regained walking ability, whereas 5 patients stayed wheelchair bound. All patients with unfavorable outcome (American Spinal Injury Association (ASIA) Impairment score [AIS] score of ≤C) showed severe pyramidal tract lesions in MEPs during the first week. All patients with normal MEPs had an excellent outcome (AIS of E, P < .05). CONCLUSIONS: Diffusion-weighted imaging (DWI) is a useful tool to confirm acute spinal ischemia suspected in patients within the first days after symptom onset. Poor outcome was associated with severe electrophysiological abnormalities in MEPs and SSEPs. Normal MEPs were significantly predictive of an excellent prognosis. A multimodal diagnostic approach combining DWI and electrophysiological evaluation facilitates the prediction of the individual clinical outcome.